If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2(3x + -1) = 15x + -2 Reorder the terms: 9x + 2(-1 + 3x) = 15x + -2 9x + (-1 * 2 + 3x * 2) = 15x + -2 9x + (-2 + 6x) = 15x + -2 Reorder the terms: -2 + 9x + 6x = 15x + -2 Combine like terms: 9x + 6x = 15x -2 + 15x = 15x + -2 Reorder the terms: -2 + 15x = -2 + 15x Add '2' to each side of the equation. -2 + 2 + 15x = -2 + 2 + 15x Combine like terms: -2 + 2 = 0 0 + 15x = -2 + 2 + 15x 15x = -2 + 2 + 15x Combine like terms: -2 + 2 = 0 15x = 0 + 15x 15x = 15x Add '-15x' to each side of the equation. 15x + -15x = 15x + -15x Combine like terms: 15x + -15x = 0 0 = 15x + -15x Combine like terms: 15x + -15x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 5/3*3 | | 3(6b-5)=-25+7b | | 4+9-4*1+8*2-5*2= | | logy=1.2 | | (x^2-5x-6)/(x-6) | | -100/1x+60=25 | | 4k+9k=-35 | | 1=4x+3*5/3-2/3x | | 2u^(-3/2)=1/5 | | x/2x=-8 | | 10*x^2-13=0 | | 5xy*6y= | | -6*x^2-x-5=0 | | 7u-2u=3u | | 1=4x+3*(5/3)-(2/3x) | | 25-4/10x | | 3y=5-2x | | x/5-3=10 | | 7x+8=5x-12 | | 1=4x+3y | | -m^2-17*m=0 | | 6x-x=60 | | -5*0=-4*4+16 | | 9u^(-4/5)=1 | | 8p-40-2p=50 | | 3*4=y+12 | | 4t+4=-21+11t | | 4+20=20 | | 2x^2-8x-42/6x^2 | | 3x^2+24x+144=0 | | 3x-2.5=7 | | -2*n+7*n-1=0 |